Morocco : Selected Issues. (IMF Staff Country Reports; Country Report, 2005)
This Selected Issues paper on Morocco analyzes Morocco's growth performance over the past thirty-five years with a special focus on the more recent past. The paper presents stylized trends in growth; it first puts the overall growth performance of Morocco in an international perspective, including an analysis of the evolution of growth volatility, and then decomposes growth by major sectors to retrospectively identify patterns of structural transformation as well as the most dynamic sectors. The paper also analyzes accumulation of factors of production and total factor productivity growth through a growth accounting exercise.